$$\dfrac{ 1-tan^245°}{1+tan^245°}$$ =

(A) tan 90°

(B) 1

(C) sin 45°

(D) 0

Asked by Pragya Singh | 1 year ago |  100

##### Solution :-

Right answer is (D) 0 .

Substitute the of tan 45° in the given equation

tan 45° = 1

$$\dfrac{ 1-tan^245°}{1+tan^245°}=\dfrac{(1-1^2)}{(1+1^2)}$$

$$\dfrac{0}{2}$$ = 0

The solution of the above equation is 0.

Answered by Abhisek | 1 year ago

### Related Questions

#### Prove the sinθ sin (90° – θ) – cos θ cos (90° – θ) = 0

Prove the sinθ sin (90° – θ) – cos θ cos (90° – θ) = 0

#### Prove that sin 48° sec 48° + cos 48° cosec 42° = 2

Prove that sin 48° sec 48° + cos 48° cosec 42° = 2

#### Prove that tan 20° tan 35° tan 45° tan 55° tan 70° = 1

Prove that tan 20° tan 35° tan 45° tan 55° tan 70° = 1

#### Evaluate the 2sin 3x = \sqrt{3}

Evaluate the $$2sin 3x = \sqrt{3}$$

#### Evalute the following: sin 20°/ cos 70°

Evalute the following:

(i) $$\dfrac{sin 20°}{ cos 70°}$$

(ii) $$\dfrac{ cos 19°}{ sin 71°}$$

(iii) $$\dfrac{sin 21°}{ cos 69°}$$

(iv) $$\dfrac{tan 10°}{ cot 80°}$$

(v) $$\dfrac{sec 11°}{ cosec 79°}$$